2010
DOI: 10.3109/0142159x.2010.496006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of instructors’ readiness for implementing e-learning in continuing medical education in Iran

Abstract: Back ground: E-learning provides new levels of flexibility in learning and teaching. This contribution of e-learning is dependent on the levels of readiness in several critical factors particularly in an educational organization. Aim: The purpose of this study was to assess instructors' readiness and to identify the most important factors that affect their readiness in e-learning in CME programs in order to use the effective opportunities that facilitate e-learning in CME programs. Methods: A 5-point Likert sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 7 publications
4
43
0
3
Order By: Relevance
“…Similar to several studies (Eslaminejad et al 2010;Heirdsfield et al 2011;Klobas and McGill 2010;Ozkan and Koseler 2009;Selim 2007;Sun et al 2008) this research showed the importance of the lecturer role in engaging students more effectively in virtual learning spheres. The findings of this study in regard to the lecturer role highlight determinants, which include: lecturers' teaching style and habits, active participation in online activities and designing appropriate tasks and assessment procedures.…”
Section: Discussionsupporting
confidence: 80%
“…Similar to several studies (Eslaminejad et al 2010;Heirdsfield et al 2011;Klobas and McGill 2010;Ozkan and Koseler 2009;Selim 2007;Sun et al 2008) this research showed the importance of the lecturer role in engaging students more effectively in virtual learning spheres. The findings of this study in regard to the lecturer role highlight determinants, which include: lecturers' teaching style and habits, active participation in online activities and designing appropriate tasks and assessment procedures.…”
Section: Discussionsupporting
confidence: 80%
“…16 One form, the flipped classroom model, is a creative strategy to promote active learning in which course material is first provided online prior to the instructor's addressing the material during class time. 19,20 For existing courses, Harris et al noted that course components to be delivered in a blended learning format should be optimized to meet students' learning needs that were not being adequately addressed in conventional classroom settings. 18 In blended learning, two studies found evidence to suggest that a better understanding of studentinstructor interactions came from considering the effectiveness of course components and the framing of the course itself.…”
mentioning
confidence: 99%
“…18 In blended learning, two studies found evidence to suggest that a better understanding of studentinstructor interactions came from considering the effectiveness of course components and the framing of the course itself. 19,20 For existing courses, Harris et al noted that course components to be delivered in a blended learning format should be optimized to meet students' learning needs that were not being adequately addressed in conventional classroom settings. 19 To do so, prior researchers have found that course instructors should first identify their learning objectives and then carefully determine how to deliver e-material and provide e-content to enhance the learning process.…”
mentioning
confidence: 99%
“…As a result, faculty, including adjunct faculty, are being called on to be accountable to maximize the educational outcomes of students just as clinicians are asked to be accountable for clinical outcomes (Schaber, 2014). Thus, effective student learning depends on the faculty's ability to appropriately design evidence-based learning experiences (Eslaminejad, Masood, & Ngah, 2010). To foster student learning, faculty must implement teaching pedagogy and strategies and be cognizant of adult learning processes (Eslaminejad et al, 2010).…”
Section: Evidence-based Teaching Practices In Allied Health Programsmentioning
confidence: 99%
“…Thus, effective student learning depends on the faculty's ability to appropriately design evidence-based learning experiences (Eslaminejad, Masood, & Ngah, 2010). To foster student learning, faculty must implement teaching pedagogy and strategies and be cognizant of adult learning processes (Eslaminejad et al, 2010). Unfortunately, allied health profession's faculty may be deficient in their knowledge and use of EBTP as illustrated in a study that found that nursing faculty could identify clinical evidence-based practice but were unaware of EBTP (Kalb, O'Conner-Von, Brockway, Rierson, & Sendelbach, 2015).…”
Section: Evidence-based Teaching Practices In Allied Health Programsmentioning
confidence: 99%